Turkey's Experience with Greenfield Gas Distribution since 2003 - World Bank (Washington, DC, 2014)
The objective of the report is to provide an assessment of Turkey's progress with gas distribution projects. The report aims to provide a detailed analysis of Turkey's current experience with gas distribution, which can possibly serve as an example for greenfield gas distribution for other countries, especially for those that are undergoing gas market liberalization. In addition, it aims to highlight some major challenges which, if addressed, will help to ensure successful progress in Turkey's gasification in the next decade. The report examines the following: specifics of Turkey 's new model for greenfield gas distribution; progress in gas distribution projects through the end of 2005 regarding the level of gasification, completed investment, and the ability of licensees to meet their requirements; Perspectives of distribution companies on major issues related to Turkey's new distribution model; major drivers of Turkey's recent experience with gas distribution; and current and potential challenges faced by the sector. The report is based on a field study conducted in Turkey in December 2005. It reflects on consultation with distribution companies representing 26 distinct distribution regions (out of the total of 35 as in the end of 2005).